The marine vegetation of the Kerguelen Islands: history of scientific campaigns, inventory of the flora and first analysis of its biogeographical affinities - Feral, Jean-Pierre; Verlaque, Marc; Rosenfeld, Sebastian; Poulin, Elie; Chenuil, Anne; Saucede, Thomas (My University, 2021)
Conceived as a baseline for the management and conservation of the marine protected area of the French Southern Territories (reserve naturelle nationale des Terres australes francaises), the checklist of marine macroalgae of the Kerguelen Islands was updated based on an extensive review of the literature and scientific databases, from the first report of the Ross expedition, in 1840, to the most recent works. This work was also conceived as a starting point for forthcoming investigations using molecular systematics tools and for monitoring the effects of global change on sub-Antarctic marine ecosystems. After a brief history of scientific campaigns, a list of 166 species was established (103 Rhodophyta, 35 Chlorophyta and 28 Ochrophyta [Phaeophyceae]). Molecular systematics studiess have shown the existence of recurrent discrepancies between the established, morphology-based taxonomy and molecular species delimitation, calling for a revision of systematics. Nevertheless, a first analysis of biogeographical affinities of the marine flora of the Kerguelen Islands is carried out and preliminary results are partially congruent with the main regions currently recognized in the Southern Ocean suggesting the importance of long-distance dispersal to explain the observed distribution patterns.
Keywords: checklist; macroalgae; rhodophyta; chlorophyta; ochrophyta -phaeophyceae; southern ocean; coastal benthos; global change; natural reserve; french southern; proteker; scientific diving